UPAYA MENINGKATKAN KEMAMPUAN KOGNITIF ANAK PADA KONSEP DASAR MATEMATIKA MELALUI PEMANFAATAN MEDIA ALAT PERAGA DI TAMAN KANAK-KANAK - Eka Khristiyanta Purnama (Fakultas Tarbiyah dan Ilmu Keguruan IAIN Purwokerto, 2012)
Abstract : The results of this action research is in the development of cognitive skills in terms of understanding the basis for early childhood learning, media is necessary utilizing such props, props and media utilization demonstration method can enhance students’ creativity and participation of children in participating in learning activities, the use of media props and demonstration methods can enhance students’ creativity and participation of children in understanding the concepts of counting, use of props and demonstrations media can improve achievement/learning of cognitive skills in children. It can be seen from the ability of the students is good compared to before the study conducted corrective learning. Key Words: Cognitive, Basic math, and media.